Daratumumab‐lenalidomide‐dexamethasone vs standard‐of‐care regimens: Efficacy in transplant‐ineligible untreated myeloma. Issue 12 (5th September 2020) - Durie, Brian G. M.; Kumar, Shaji K.; Usmani, Saad Z.; Nonyane, Bareng A. S.; Ammann, Eric M.; Lam, Annette; Kobos, Rachel; Maiese, Eric M.; Facon, Thierry
Abstract: Daratumumab in combination with lenalidomide‐dexamethasone (D‐Rd) recently received FDA approval for the treatment of transplant‐ineligible patients with newly diagnosed multiple myeloma (NDMM). The present PEGASUS study compared progression‐free survival (PFS) in patients treated with D‐Rd in the MAIA trial and patients treated with common standard‐of‐care regimens from the Flatiron Health electronic health record‐derived deidentified database, which has data from patients treated primarily at community‐based oncology practices in the United States. Individual‐level patient data from both data sources were used to perform an anchored indirect treatment comparison (ITC) of D‐Rd to bortezomib‐lenalidomide‐dexamethasone (VRd) and bortezomib‐dexamethasone (Vd); lenalidomide‐dexamethasone (Rd) was the common anchor for the ITC. Hazard ratios (HRs) reflecting direct comparisons of PFS within MAIA (D‐Rd vs Rd) and Flatiron Health (VRd vs Rd; Vd vs Rd) were used to make ITCs for D‐Rd vs VRd and Vd, respectively. After application of MAIA inclusion/exclusion criteria and propensity‐score weighting, the Flatiron Health patients resembled the MAIA trial population on measured baseline characteristics. Based on the direct comparison within MAIA, treatment with D‐Rd was associated with a significantly lower risk of progression or death compared to Rd (HR 0.54; 95% CI 0.42, 0.71). Based on the ITCs, D‐Rd was associated with a significantly lower risk of progression or death compared to VRd (HR 0.68; 95% CI 0.48, 0.98) and Vd (HR 0.48; 95% CI 0.33, 0.69). In the absence of head‐to‐head trials comparing D‐Rd to VRd or Vd, the present ITC may help inform treatment selection in transplant‐ineligible patients with NDMM.